Pemodelan Sistem Traceability Supply Chain Management Halal menggunakan Interpretive Structural Modeling PT.XYZ - 10070216108, Fajar Ainul Yaqien; Ceha, Rakhmat (Bandung Conference Series: Industrial Engineering Science, 2024)
Abstract. XYZ chicken slaughterhouse is a chicken slaughterhouse that was established in 2013 in Banjar. In carrying out its production activities, RPA XYZ gets supplies from their farms, which can produce 3000 pieces per day. RPA XYZ has problems with manual recording, no supply chain tracking and no guarantee of halal products to encourage increased consumer confidence in slaughtered chicken products. Therefore, a traceability system was designed for the chicken meat supply chain to ensure the halal of chicken meat. In addition, Interpretative Stuctural Modeling (ISM) modeling is also used to assess the level of relationship between elements of activities during the production process with the aim of increasing the halal slaughter chicken products. The result of the research is the existence of a product tracebalility model by applying technology to business actors to improve the supply chain system of halal products adapted to Industry 4.0 conditions. Business process improvement, in this series of supply chain processes utilizes modern technology in addition to QR, RFID and GPS technology, to facilitate traceability and maintain halal integrity of slaughtered chicken. Abstrak. Rumah pemotongan ayam XYZ merupakan tempat pemotongan ayam yang berdiri sejak 2013 di Banjar. Dalam melaksanakan kegiatan produksinya RPA XYZ mendapatkan pasokan dari peternakan mereka, dimana dapat memproduksi 3000 potong perharinya. RPA XYZ mempunyai permasalahan pencatatan manual, belum adanya pelacakan rantai pasok dan belum ada jaminan halal produk untuk mendorong peningkatan kepercayaan konsumen terhadap produk ayam potong. Maka dari itu dirancang sistem traceability terhadap rantai pasok daging ayamnya untuk menjamin kehalalan daging ayam. Selain itu, digunakan juga pemodelan Interpretative Stuctural Modelling (ISM) untuk menilai tingkat hubungan elemen-elemen kegiatan selama proses produksi dengan tujuan peningkatan kehalalan produk ayam potong. Hasil dari penelitian yaitu adanya model tracebalility produk dengan menerapkan teknologi pada pelaku usaha untuk memperbaiki sistem rantai pasok produk halal yang disesuaikan dengan kondisi Industri 4.0. Perbaikan proses bisnis, pada rangkaian proses rantai pasok ini memanfaatkan teknologi modern di atarnaya penambahan teknologi QR, RFID dan GPS, untuk memepermudah traceability dan mejaga intergritas halal ayam potong.